SONG CREATION ON RESILIENCE TO INCREASE SELF ESTEEM IN YOUNG ADULTS - Ayesha R. Imara; Patricia Vicky Sihombing (Jurnal Scientia, 2023)
People with low self-esteem tend to withdraw from trying because they simply feel they do not have the skill to do it. There are many cases of low self-esteem in the world including Indonesia. This project aims to improve self esteem in the audience through a song. The target audience of this project is for Young Adults. The project stages include pre-production, production and post-production. The song creation on Resilience has the title of “Remedy For My Soul”. The creator chose that topic because the song revolves around Resiliency. This song explains someone who has the courage to change and is willing to move on from their past experience. Change all the negative and toxic traits and twist the bad experience that caused the trauma that lead them to low self esteem with their major comeback of the best version of themselves full of confidence, acceptance, resiliency and higher self esteem. This song was written on October 5th 2021 by Ayesha. The making of this song took around 5 months to do, the lyrics and the guided guitar was made by the creator and was arranged together with the Suarasuku Studio Team from January 20th 2022 – end in the help of Suarasuku Studio. Tegi Merkuri mastered this song on May 19th 2022 and will be published on June 10th 2022 through 55 digital platforms.